Mother tongue education in Nepal: a scoping review of research, policy, and budget priorities - Pariksha Onta; Amado M. Padilla (Frontiers in Education, 2026)
Nepal's language policy has evolved from a historically exclusionary “one nation, one language” philosophy to a constitutionally enshrined commitment to multilingualism. This scoping review traces how mother tongue (MT) education is positioned alongside the growing influence of English-medium instruction. Drawing on 111 documents synthesized through VOSviewer visualizations, we mapped the scholarly discourse surrounding MT education and language policy. Government policy documents were then analyzed to examine how they have supported or plan to support MT education, and budget speeches from the Ministry of Finance (2016/2017–2026/2027) were reviewed to assess the extent to which MT education and preservation have been addressed in national financing priorities. The findings revealed a persistent disconnect between constitutional commitments, classroom practice, and targeted funding. The review highlights the need for a shift from top-down policy mandates toward community-centered designs driven by local linguistic expertise, offering an accessible, evidence-based entry point into the documented record on language and education.